2023
DOI: 10.3390/aerospace10010081
|View full text |Cite
|
Sign up to set email alerts
|

Air Traffic Management as a Vital Part of Urban Air Mobility—A Review of DLR’s Research Work from 1995 to 2022

Abstract: Urban air mobility is a rapidly growing field of research. While drones or unmanned aerial vehicles have been operated mainly in the private and military sector in the past, an increasing range of opportunities is opening up for commercial applications. A new multitude of passenger-carrying drone or air taxi concepts promises to fulfill the dream of flying above congested urban areas. While early research has been focusing on vehicle development, solutions for urban air traffic management are lagging behind. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The article [8] proposes a layered system approach in order to organize airspace for UAM vehicles, depending on the vehicle type, level of autonomy, and altitude. Various ATM programs within German Aerospace Center (DLR) initiatives are discussed by the authors in [9]. The authors in [10] propose an assessment model for vehicleobstacle collision hazards.…”
Section: Related Workmentioning
confidence: 99%
“…The article [8] proposes a layered system approach in order to organize airspace for UAM vehicles, depending on the vehicle type, level of autonomy, and altitude. Various ATM programs within German Aerospace Center (DLR) initiatives are discussed by the authors in [9]. The authors in [10] propose an assessment model for vehicleobstacle collision hazards.…”
Section: Related Workmentioning
confidence: 99%
“…As these airtaxis do have the option to be electrically powered (cf. [3], ch. 4), reduced travel times in combination with environment-friendly transport are possible.…”
Section: Motivationmentioning
confidence: 99%
“…DLR) in the project HorizonUAM (cf. [3]). Based on the example of Hamburg, e cient airway and landing spot design was achieved as shown in Figure 1 (cf.…”
Section: Existing Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid growth of the UAV industry has created a psychological fear of the unknown among communities (Çetin et al, 2022). In this context, the integration of UAVs into existing systems under the UAM framework should consider not only technical aspects such as design, certification, operational aspects, and infrastructure requirements but also public acceptance (Schuchardt et al, 2023). Some research evaluating public acceptance of UAVs in urban logistics has shown a positive attitude toward the use of these vehicles (Melo et al, 2023).…”
Section: Literaturementioning
confidence: 99%